3014 Identification of a Cohort to Study Treatment Patterns in Elderly Patients with Incident Hodgkin Lymphoma (HL) using Surveillance, Epidemiology and End Results (SEER)-Medicare Data. (27th March 2019) - Rodday, Angie Mae; Hahn, Theresa; Lindenauer, Peter; Parsons, Susan
Abstract : OBJECTIVES/SPECIFIC AIMS: (1) To define and describe a cohort of patients aged ≥65 years with incident HL from SEER-Medicare data. (2) To identify patient, disease, and system-level factors associated with initial treatment for HL. METHODS/STUDY POPULATION: This retrospective cohort study utilized SEER-Medicare data from 1999-2014. Patients with incident classical HL were identified using SEER registry histology groupings. The cohort was restricted to those with Medicare Part A and B fee-for-service for 3 months prior to and 1 year after diagnosis (or until date of death) in order to fully capture claims for outpatient chemotherapy. Patients were excluded for the following reasons: missing month of HL diagnosis; unknown diagnostic confirmation; reporting from autopsy or death certificate; or another cancer diagnosis +/− 2 years of the HL diagnosis. Demographic and disease characteristics were defined based on SEER registry data. Broad treatment categories were defined using SEER data, while detailed treatment categories will be defined based on Medicare claims. Length of follow-up was defined as the number of months until the earliest of the following: death; end of continuous Medicare Part A and B fee-for-service enrollment; or the end of the available data (12/31/2014). Demographic, disease, and preliminary treatment characteristics were described for the cohort. Future analyses will explore patient and disease factors, including comorbidities and an estimate of frailty, as well as system-level factors associated with initial treatment of HL. RESULTS/ANTICIPATED RESULTS: We identified 2909 patients meeting eligibility for the cohort. The median length of follow-up was 22 months (Q1=5, Q3=62). Median age was 75.9 years (Q1=70, Q3=81), 49.6% were female, and 82.6% were non-Hispanic/White. Only 11.5% of patients were in rural or non-urban areas. 13.8% of patients were dual eligible for both Medicare and Medicaid. Nodular sclerosis was the most common histology (35.2%), followed by mixed cellularity (21.1%); 36.5% had histology that was not otherwise specified. Patients were evenly distributed across Ann Arbor Stage (21.8% with I; 22.3% with II; 25.8% with III; 24.2% with IV; 6% unknown). B symptoms were present in 35.2% of patients, absent in 39.6%, and unknown in 25.2%. Neither tumor bulk nor international prognostic score were available via SEER registry data. According to SEER registry data, most patients received some treatment for their HL (81.9%) and 75% of those patients initiated treatment within one month of diagnosis. 72% of patients died with median time to death of 9 months (Q1=3, Q3=43). DISCUSSION/SIGNIFICANCE OF IMPACT: We successfully identified and described a cohort of 2909 older patients with incident HL from the SEER-Medicare data. This provides a unique opportunity to study this cohort in a large, representative dataset with nearly 15 years of follow up. Future analysis will help us to better understand treatment patterns of HL in older patients and factors associated with treatment. These results can then be used to help improve care decisions and clinical outcomes.